Shear Bond Strength Comparison of Three Different Orthodontic Adhesives - M. Oğuz Öztoprak; Göksu Trakyalı; Derya Germeç-Çakan; Didem Nalbantgil; Tülin Arun (Galenos Yayinevi, 2010)
Aim:The purpose of this study was to evaluate and compare the shear bond strengths (SBS) and fracture mode of three different orthodontic adhesive systems.Materials and Methods:Sixty bovine permanent mandibular incisor teeth were randomly divided into three groups of 20. All teeth were etched with 37 per cent phosphoric acid for 15 seconds, rinsed and air dried. Mandibular incisor brackets were bonded to the prepared enamel using three different adhesives (Eagle Bond, Transbond XT, and Resino-mer/OS+) and light cured. Bonded samples were thermocycled. Shear forces were applied to samples with a testing machine. Data obtained in megapascals were analyzed with descriptive statistics and with ANOVA and post Hoc Tukey multiple comparison test. The adhesive fracture site was classified with the Adhesive Remnant Index (ARI).Results:SBS of Re-sinomer/OS+ was found to be statistically significantly greater than Eagle Bond and Transbond XT. The comparisons of the ARI scores between the three groups indicated that bracket failure mode was significantly different among groups (P<0.001). Bond failure occurred mostly at the adhesive-enamel interface for Resi-nomer/OS+, whereas in Eagle Bond and Transbond XT the failure site was within the adhesive.Conclusion:Resino-mer/OS+ exhibited a significantly higher SBS compared to the other two products; however enamel fractures were observed during debonding. Therefore, clinicians should be careful when removing bonded brackets with this adhesive.